2015
DOI: 10.1049/iet-pel.2013.0911
|View full text |Cite
|
Sign up to set email alerts
|

Active damping method to reduce the output impedance of the DC–DC converters

Abstract: In the cascaded power system, instability may occur because of the impedance interaction. The system can be stabilised by passive damping or control methods to reduce the output impedance of the source converter and improve the damping characteristics. This study focuses on the source converter in the cascaded system and presents a new active damping control to reduce the output impedance of the converter by a proper active damping controller. The method to compute the corresponding active damping controller i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…1, the FS DAB converter behaves like a source with equivalent output impedance notated as Z F,o when power flows in the forward direction. Value of Z F,o varies with the frequency of output current [24], and will usually be non-zero. It will thus interact with input impedance Z F, in of the FR three-phase inverter, which behaves like a load [25].…”
Section: Overview Of Impedances and Their Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, the FS DAB converter behaves like a source with equivalent output impedance notated as Z F,o when power flows in the forward direction. Value of Z F,o varies with the frequency of output current [24], and will usually be non-zero. It will thus interact with input impedance Z F, in of the FR three-phase inverter, which behaves like a load [25].…”
Section: Overview Of Impedances and Their Interactionsmentioning
confidence: 99%
“…Forward and reverse impedances of the inverter are significantly different under power control. As discussed in [22–24, 39, 40], the negative impedance will introduce instability factor to the system, so it is appropriate for studying impedance interactions documented in the following section.…”
Section: Derivation Of Impedancesmentioning
confidence: 99%
“…Finally, it can be observed that the numerator of the input control-to-input current (27) presents no terms regarding the output duty cycle. The same can be noted from the numerator of the output control-to-output current (31) which disregards the effects of the input duty ratio, being a consequence of the averaged model previously expressed.…”
Section: Control Transfer Functionsmentioning
confidence: 98%
“…Oscillations can be damped by inserting a virtual impedance at the output of voltage-regulating converters to offset the negative resistance of CPLs [11]. In [12][13][14], a converter introduces a virtual resistor by feeding the output current back to the voltage control loop, which simulates the passive damping control method. A virtual capacitance control system is introduced [15][16][17].…”
Section: Introductionmentioning
confidence: 99%